Prevention of General Criminal Offenses In The General Criminal Investigation Directorate of The Maluku Regional Police Force - Pasorong, Wiranata; Titahelu, Juanrico Alfaromona Sumarezs; Latupeirissa, Julianus Edwin (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Security and order is a situation characterized by guaranteed security and public order, order and law enforcement, and the implementation of protection, protection and services to the community.  One of the police divisions in having an important task to emphasize general crimes or crimes of a general nature contained in Maluku carried out by the Directorate of General Criminal Investigation by carrying out prevention efforts.Purposes of the Research: This study aims to examine and discuss the Prevention of General Crimes at the General Criminal Investigation Directorate of the Maluku Regional Police.Methods of the Research: The research method used is normative research, statutory approach, primary and secondary legal materials and material collection procedures using literature studies. the approaches used are: statute approach, conceptual approach, and casus approach. The technique of searching for legal materials uses document study techniques, and analyzes the study using qualitative analysis.Findings of the Research: The results showed that. Prevention of General Crimes Carried out by the General Criminal Directorate of Maluku Police is to increase parents' awareness to play a greater role in fostering their children, provide information and remind the public of the criminal threats that can be imposed on everyone who commits acts that can be categorized as despicable acts, provide. intensify religious and moral education to all levels of society outside of school and provide education and transparency in law enforcement; and try to improve the ability and authority of law enforcement officials in handling criminal acts through training activities and other activities that are really felt directly by the community.